Cooperativism and social justice for the post-conflict: Integration from the solidarity economy for the generation of peace territories starting from the regions - Doria Orozco, Teddy (Cooperativismo & Desarrollo, 2017)
Purpose: The present paper seeks to answer the questions: how can cooperativism and social justice be part of Colombia’s post-conflict situation? And how may integration from the solidarity economy help to create peace territories starting from the regions? Description: A brief historical approach to cooperativism in Colombia is carried out to analyze the development of solidarity economy in the country pointing to a post-conflict situation and to the generation of peace territories starting from the regions. Point of view: In the process of building a stable and lasting peace starting from the regions, it is necessary to contemplate the advantages of cooperativism and social justice, since they allow strengthening the social fabric through the consolidation of experiences with the practice of values and principles of the solidarity sector. These offer a pattern for the regional integration, thus becoming the exemplary substratum that responds to the social reintegration, reconciliation and progress of those who need it most. Conclusions: The proper implementation of the values and principles of the solidarity sector mark a point of reference for regional integration, contribute to social reintegration, reconciliation and social progress.